Characterization of Plasma Protein Alterations in Pregnant and Postpartum Individuals Living With HIV to Support Physiologically-Based Pharmacokinetic Model Development - Zhao, Sherry; Gockenbach, Mary; Grimstein, Manuela; Sachs, Hari Cheryl; Mirochnick, Mark; Struble, Kimberly; Belew, Yodit; Wang, Jian; Capparelli, Edmund V.; Best, Brookie M.; Johnson, Tamara; Momper, Jeremiah D.; et al. (Frontiers in Pediatrics, 2021)
Background: Alterations in plasma protein concentrations in pregnant and postpartum individuals can influence antiretroviral (ARV) pharmacokinetics. Physiologically-based pharmacokinetic (PBPK) models can serve to inform drug dosing decisions in understudied populations. However, development of such models requires quantitative physiological information (e.g., changes in plasma protein concentration) from the population of interest. Objective: To quantitively describe the time-course of albumin and α1-acid glycoprotein (AAG) concentrations in pregnant and postpartum women living with HIV. Methods: Serum and plasma protein concentrations procured from the International Maternal Pediatric Adolescent AIDS Clinical Trial Protocol 1026s (P1026s) were analyzed using a generalized additive modeling approach. Separate nonparametric smoothing splines were fit to albumin and AAG concentrations as functions of gestational age or postpartum duration. Results: The analysis included 871 and 757 serum albumin concentrations collected from 380 pregnant (~20 to 42 weeks gestation) and 354 postpartum (0 to 46 weeks postpartum) women, respectively. Thirty-six and 32 plasma AAG concentrations from 31 pregnant (~24 to 38 weeks gestation) and 30 postpartum women (~2-13 weeks postpartum), respectively, were available for analysis. Estimated mean albumin concentrations remained stable from 20 weeks gestation to term (33.4 to 34.3 g/L); whereas, concentrations rapidly increased postpartum until stabilizing at ~42.3 g/L fifteen weeks after delivery. Estimated AAG concentrations slightly decreased from 24 weeks gestation to term (53.6 and 44.9 mg/dL) while postpartum levels were elevated at 2 weeks after delivery (126.1 mg/dL) and subsequently declined thereafter. Computational functions were developed to quantitatively communicate study results in a form that can be readily utilized for PBPK model development. Conclusion: By characterizing the trajectory of plasma protein concentrations in pregnant and postpartum women living with HIV, our analysis can improve PBPK model predictions for HIV antiretrovirals and better inform drug dosing decisions in this understudied population.